Sleep, Negentropy and Consciousness - Remler, Michael (Journal of NeuroPhilosophy, 2026)
Circadian rhythms of alternating metabolic patterns homologous to those seen in the human sleep wake cycle are ubiquitous in virtually all life forms. Negative entropy metabolic activity, negentropy, the importation of high energy compounds and the elimination of low energy residua, used to maintain a low internal entropy environment is similarly ubiquitous. The metabolic cycle, as internalized across the life forms, functions to sequester portions of the negative entropy process which would interfere with each other if attempted simultaneously. Information is the essence of low entropy. Evolution is associated with the progressive increase in the direct importation of information and the utilization of that information to maintain low internal entropy. While 'Information is Physical', its management and storage, requires energy, alternative stored information do not differ in enthalpy but only in meaning. The only way to process and store information negentropy is to be aware of the information, understand the information, have the free will to choose and the ability to control the matter of the brain to affect that choice. The capacities which define the essence of Consciousness, are the same as those essential for Information Negentropy. In humans, the process that manages negentropy through wakefulness and sleep is continuous in its identity, also through some coma, dementia and some psychosis. The deeper understanding of Consciousness must transcend not only its various modes of function but more so its necessity to understand meaning in order to perform negentropy.